1991
DOI: 10.1042/bj2760027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in insulin-receptor structure associated with trypsin-induced activation of the receptor tyrosine kinase

Abstract: The tyrosine kinase of the insulin receptor can be activated by trypsin treatment. The concomitant abolition of insulin binding has been postulated to result from proteolytic destruction of the receptor. A discrepancy between the decrease in insulin binding and receptor immunoreactivity after trypsin treatment led us to investigate more closely the structure of the trypsin-treated receptor. After trypsin treatment of the CHOT cell line, which over-expresses transfected human insulin receptors, insulin binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…This discrepancy may be largely due to di erent experimental procedures: in the previous report, cells were trypsinized and then kept in suspension for 30 min. In our experiments, cells were detached by Versene, since, as mentioned above, trypsinization is known to partially digest the extracellular portions of growth factor receptors (Clark et al, 1991). Also at variance with other experimental situations, we found a lack of correlation with the serine/threonine kinase Akt, activation which has also been shown to be important in protection from apoptosis, including IGF-I mediated protection (Kennedy et al, 1997;Khwaja et al, 1997;Datta et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This discrepancy may be largely due to di erent experimental procedures: in the previous report, cells were trypsinized and then kept in suspension for 30 min. In our experiments, cells were detached by Versene, since, as mentioned above, trypsinization is known to partially digest the extracellular portions of growth factor receptors (Clark et al, 1991). Also at variance with other experimental situations, we found a lack of correlation with the serine/threonine kinase Akt, activation which has also been shown to be important in protection from apoptosis, including IGF-I mediated protection (Kennedy et al, 1997;Khwaja et al, 1997;Datta et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
“…In preliminary experiments (not shown), we had observed that detachment of cells by trypsinization (as it is usually done also in our laboratory) caused the results to be somewhat erratic, probably due to the fact that trypsinization, even modest, induces partial breakdown of the extracellular part of growth factor receptors (Clark et al, 1991). p6 cells (mouse embryo ®broblasts that over-express the human IGF-IR) were chosen for the initial experiments, because they are known to form colonies in soft agar very e ciently (Pietrzkowski et al, 1992), and to grow in anchorageindependent conditions in vivo .…”
Section: Resultsmentioning
confidence: 78%
“…As reported by other investigators, only receptors exposed to the extracellular medium are accessible to trypsin [4,23 26]. This treatment proteolyzes the ~-subunit of the receptor in a unique site close to the C-terminus of the ~-subunit and separates both subunits [27]. The larger fragment resulting from this treatment (100 kDa) contains both the mAb 83-7 and insulin binding sites, whereas the smaller fragment remains attached to the fl-subunit of the receptor [27].…”
Section: Resultsmentioning
confidence: 80%
“…These antibodies have been extensively described by Clark et al [27]. Anti-phosphotyrosine antibody 4GI0 was purchased from Upstate Biotechnologies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation